1996
DOI: 10.1016/s0014-5793(96)01153-2
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical course of hydrolysis catalyzed by arabinofuranosyl hydrolases

Abstract: 1~ IntroductionEnzymic hydrolysis of glycosidic linkages occurs via two m ~jor mechanisms, which result in either net retention or inversion of anomeric configuration [1]. Both hydrolytic mechmisms involve general acid catalysis and require two critical reddues (a proton donor and a nucleophile/base), which in m 9st glycosyl hydrolases are aspartate and/or glutamate resid~es 2.1.99)hydrolyse the (1 ~ 5)-C~-L-arabinofuranosyl linkages in linear arabinan in a random pattern, initially releasing arabinotriose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 48 publications
2
40
0
5
Order By: Relevance
“…To confirm this assignment, the new reaction product was purified and characterized by 1 H NMR. The observed multiplicity of the anomeric proton (doublet at 4.74 ppm), and its coupling constant (J 1,2 ϭ 1.6 Hz), is consistent with the product being methyl ␣-L-arabinofuranoside (15).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…To confirm this assignment, the new reaction product was purified and characterized by 1 H NMR. The observed multiplicity of the anomeric proton (doublet at 4.74 ppm), and its coupling constant (J 1,2 ϭ 1.6 Hz), is consistent with the product being methyl ␣-L-arabinofuranoside (15).…”
Section: Resultssupporting
confidence: 59%
“…Interestingly, further incubation of the reaction resulted in the hydrolysis of the new product by the enzyme, yielding arabinofuranoside and methanol. The hydrolysis of the methyl ␣-L-arabinofuranoside product was also observed in the case of arabinofuranosidase A from Aspergillus niger (15). This simple TLC-based approach to determine the stereochemical course of hydrolysis can be easily applied to other glycoside hydrolases with unknown stereochemistry.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Enzymes in CAZy that hydrolyze polysaccharides are named after their substrate, GH family, the initials of the organism of origin and given a letter to indicate the order in which they were first reported (Henrissat et al, 1998 1,5--L-arabinanase (AnArb43A) were shown by NMR to use a single displacement mechanism resulting in products with inverted anomeric configuration (Pitson et al, 1996;Wilkens et al, 2016).…”
Section: Classification Of -L-arabinofuranosidasesmentioning
confidence: 99%